Pharmaceutico – Evaluation of Pathyadi Varti Anjana Containing Moringa Oleifera Seeds: An Analytical Perspective - kumar goud , Prem; thakur, Akanksha; dhanaji bhosale , Shreya; rajagopala , Manjusha (International Research Journal of Ayurveda & Yoga, 2025)
Background: Blur vision, particularly due to cataracts, remains a significant global public health concern, especially in rural and underserved populations. Ayurvedic formulations such as Pathyadi Varti (PV), which comprises four potent herbo-mineral ingredients with psycho-physical Kaphahara properties, have shown promise in addressing age-related ocular degeneration. This study evaluates the physicochemical properties, organoleptic characteristics, and phytochemical composition of PV.